EFFECT OF RINSED WITH Psidium guajava LINN LEAVES DECOCTION ON PLAQUE INDEX AND SALIVARY pH ON STUDENTS OF SMPN 29 PALEMBANG - Claudine Radot Pamela Boru Tambunan; Misnaniarti Misnaniarti (Universitas Pahlawan, 2021)
Background: Dental plaque is a structurally and functionally organized biofilm. Caries is a disease that caused by acids from bacterial metabolism. Psidium guajava Linn leaves decoction contains flavonoid, tannin, and saponin that can reduce plaque accumulation and phosphate that can neutralize salivary pH. The aim of this study was to evaluate the effect of rinsed with Psidium guajava Linn leaves decoction on plaque index and salivary pH. Method: This experimental research was done with pretest and posttest control group design involving 102 students of SMPN 29 Palembang. Subjects were divided into 3 groups, group I (Psidium guajava Linn leaves decoction), group II (chlorhexidine 0,06%), group III (distilled water). Subjects were instructed to rinse with 10 ml of mouthrinse twice a day for 7 days. At baseline and 7 days plaque was assessed using Turesky-Gilmore-Glickman modification of Quigley Hein index. Saliva was collected with spitting method and salivary pH was measured with digital pH at baseline and 7 days. Data was analyzed with paired t-test, one way ANOVA, Wilcoxon, and Kruskal-Wallis. Result: There was a significant decrease in plaque index and a significant increase in salivary pH on group I (p